2008
DOI: 10.1016/j.apcata.2007.09.035
|View full text |Cite
|
Sign up to set email alerts
|

New catalytic materials for the high-temperature synthesis of hydrocyanic acid from methane and ammonia by high-throughput approach

Abstract: For converting methane and ammonia to hydrocyanic acid, catalysts were prepared and tested in a 48-parallel channel fixed-bed reactor unit operating at temperatures up to 1373 K. The catalysts were synthesized with a robot applying a genetic algorithm as the design tool. New and improved catalyst compositions were discovered by using a total of seven generations each consisting of 92 potential catalysts. Thereby, the catalyst support turned out as an important input variable. Furthermore, platinum, which is we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 21 publications
1
27
0
1
Order By: Relevance
“…However, high throughput experimentation combined with genetic algorithm, analysis of variance and regression trees revealed that additives such as Ir, Au, Ni and Re and also alternative supports such as Si 3 N 4 or SiC have a positive effect on the HCN yield [52]. Addition of oxygen to a CH 4 =NH 3 feed enhances HCN formation rate by several orders of magnitude.…”
Section: Methane To Hydrogen Cyanidementioning
confidence: 99%
“…However, high throughput experimentation combined with genetic algorithm, analysis of variance and regression trees revealed that additives such as Ir, Au, Ni and Re and also alternative supports such as Si 3 N 4 or SiC have a positive effect on the HCN yield [52]. Addition of oxygen to a CH 4 =NH 3 feed enhances HCN formation rate by several orders of magnitude.…”
Section: Methane To Hydrogen Cyanidementioning
confidence: 99%
“…During the last decade, high-throughput (HT) methods have become an established tool for the evaluation of heterogeneous catalysts for different chemical processes [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. hte's approach to HT testing is based on a patent filed on 3 March 1998, which relates to parallel reactor systems for testing the activity of solid catalysts simultaneously exposed to gaseous feed streams [17].…”
Section: Introductionmentioning
confidence: 99%
“…Baerns et al have studied the oxidative dehydrogenation of propane, using gaseous oxygen, [22][23][24] total propane oxidation, [25] and the production of hydrocyanic acid. [26] Yamada et al have investigated methanol synthesis, [27][28][29] and others have performed studies on (selective) oxidation, [30][31][32][33] reduction, [34] methane reforming, [35] and isomerisation. [36] Most of the catalysts used in these studies are mixed oxides containing four to five different metals.…”
Section: Qcementioning
confidence: 99%